Effect of Strobilanthes crispus extract and individual polyphenols on lipolysis - Zawawi, Norhasnida (2011)
Obesity is a disease that has reached epidemic proportions across the world. Many types of treatments have been used to combat obesity including using synthetic drugs such as sibutramine and orlistat. However, the high cost and potentially hazardous side-effects of anti-obesity drugs have led many researchers to turn to naturally occurring compounds obtained from fruits, vegetables, herbs and plants for the treatment of obesity. In our study, the anti-obesity effects of S. crispus crude extract (SCE) and individual polyphenols (EGCG, Resveratrol, Phloridzin, Quercetin and Verbascoside) found in fruits, vegetables and herbs have been investigated.